2007
DOI: 10.1088/0031-8949/76/4/016
|View full text |Cite
|
Sign up to set email alerts
|

Radioactive decay by the emission of heavy nuclear fragments

Abstract: Radioactive decay of nuclei by the emission of heavy ions of C, N, O, F, Ne, Na, Mg, Al, Si, and P isotopes (known as exotic decay or cluster radioactivity) is reinvestigated within the framework of a semiempirical, one-parameter model based on a quantum mechanical, tunnelling mechanism through a potential barrier, where both centrifugal and overlapping effects are considered to half-life evaluations. This treatment appeared to be very adequate at fitting all measured half-life values for the cluster emission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 63 publications
0
16
0
3
Order By: Relevance
“…So far, the emission of 22 Ne, 24 Ne, 25 Ne, 26 Ne, 28 Mg, 29 Mg and 30 Mg clusters from 230,232−236 U isotopes have been experimentally confirmed [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, the emission of 22 Ne, 24 Ne, 25 Ne, 26 Ne, 28 Mg, 29 Mg and 30 Mg clusters from 230,232−236 U isotopes have been experimentally confirmed [8].…”
Section: Introductionmentioning
confidence: 99%
“…Santhosh et al [26][27][28] have calculated half-lives for experimentally observed cluster decay modes of several heavy nuclei in the trans-lead region by using Coulomb Proximity potential model [CPPM]. Tavares et al [29] have investigated exotic decay of heavy nuclei within the framework of a semi-empirical, one-parameter model based on a quantum mechanical, tunneling mechanism through a potential barrier by taking into account both centrifugal and overlapping effects in half-life evaluations. Warda and Robledo [30] have recently studied CR of actinide nuclei by using mean-field Hartree-Fock-Bogoliubov theory with the phenomenological Gogny interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Para mais detalhes sobre a descoberta do CBPF e para posteriores comprovações experimentais e avanços teóricos, ver, por exemplo, Tavares e cols. [48].…”
unclassified
“…Como dissemos, as descobertas de Lattes foram capitaneadas por um grupo de cientistas -apoiado por intelectuais, artistas, empresários, jornalistas e militares nacionalistas -cujo objetivo principal era impulsionar a criação de um centro nacional de pesquisa básica em física. 48 Ainda no plano internacional,é preciso lembrar que a energia nuclear passou a ser vista, depois da Segunda Guerra, como instrumento de poder e autonomia política pelos governos.…”
unclassified
See 1 more Smart Citation